Penyediaan Sistem Informasi Menejemen Pegawai Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Pekanbaru Dalam Mendukung Kebijakan E-Government Pada Tahun 2019 - Ramlan Darmansyah; Tito Handoko; Mohammad Yohamzy Tiyas Tinov (Bahasa Indonesia, 2020)
E-Government policy is to reduce the use of manual systems or the use of paper in any service. The existence of information technology policy in the government environment is expected to realize the e-government is transparent and efficient . The purpose of this research is 1). To know the provision of Officer management information system on personnel Agency and Human resources development Pekanbaru in support of e-government policy in years 2019 and 2.) To know the supporting factors providing information Systems Management officer on personnel agency and Human resource development Pekanbaru City in support of e-government policy in year 2019. The method used in this study uses a qualitative approach, this type of research is the study of literature where data sources are obtained from legal products, journal articles, related documents and mass media sources. Research is conducted on personnel agency and Human resources development. The result of this research is the application of Program management Information system officers implemented by the Agency of personnel and human resources development is in addition to realizing the government-based e-Government also supports the policy of Pekanbaru mayor. The existence of e-government support in providing application of staff management information system at personnel agency and Human resources Development Pekanbaru City.